A study on knowledge attitude and practice of colorectal cancer screening in west Malaysia - Harmy, Mohamed Yusoff (Pusat Pengajian Sains Kesihatan, 2013)
In Malaysia, colorectal cancer accounts for 142% of ma.le cancers makin~ i! the commonest earjcer in mafes. It is the third most common canter amorig women ( 10.1% of female cancers).lt is proven that mortality due to colorectal cancer and incidence of m;;liignantneoplasmcari be effectively reduced with early diagnosis. However despite the availabrlity of screaning motlalities, · · almost 80% of Malaysian sought treatment for cancer only when they were already in late stage. It could be due to patient's ignorance or negative attitude of the primary hea.lth care personels · toward colorectal cancer screening. This study was conducted to determine the knowledge, attitude and practice of colorecti!l cancer screening among primary health care providers and moderate risk patients iri west Malaysia. It is a cross sectional study involving 44 Health clinic in West Malaysia, A total of 116 primary health care providers and 1905 moderate risk patients were enrolled in this study. Generally the understanding about colorectal cancer screening is very low among moderate risk · patient. Only 7 % of them know about FOBT and colonoscopy and only 3 % of them had good . attitude score. We also found that only 0.7 %of patient who should undergone screening had it done. For primary health care providers, despite having reasonable knowledge on clorectal cancer screening, their attitude score is very low . Only 1. 7 % of them had good attitude score. Only 20 % of them are performing some form of colorectal cancer screening in their practice.